(untitled) (Journal of Agriculture & Rural Development, 2008)
Five exotic carp species viz. Hypophthalmichthys molitrix, Cyprinus carpio var. specularis, Cyprinus idellus, Cyprinus carpio var. communis and Puntius gonionotus were examined for parasitic diseases out of which 793 fishes were infected by 3 protozoan (Trichodina sp., Ichthyophthirius sp. and Chilodonella sp.), 2 monogenean (Gyrodactylus sp., Dactylogyrus sp.), 2 trematoda (Gorgotrema sp., Metadena sp.), 4 cestoda (Rhopalothyrax sp., Marsipometra sp., Lytocestus sp. and Senga sp.), 2 nematoda (Camallanus sp., Procamallanus sp.), 3 crustacean (Argulus sp., Alitropus sp. and Lamproglena sp.) and 1 insect (Dipteran larvae) parasitic species. These parasites were isolated from body slime, gills and intestine of the infected fishes. In general species wise parasitic average prevalence was highest in Argulus sp. (20.07%) in H. molitrix and lowest in Metadena sp. (2.85%) in C. carpio var. communis. Average abundance was highest in Argulus sp. (0.70) in H. molitrix and lowest was in Lamproglena sp. (0.04) in C. carpio var. communis. Average mean density was highest in Chilodonella sp. (10.00) in C. carpio var. specularis and lowest in Procamallanus sp. (2.08) in C. carpio var. communis. Key words: Parasites, diseases, exotic carp. DOI = 10.3329/jard.v5i1.1469 J Agric Rural Dev 5(1&2), 127-134, June 2007